The System of Collective Security - Softić, Sakib (Kriminalističke teme, 2012)
This article deals with international protection of peace and security known as Collective Security, established by the Charter of UN. The Charter of UN accepts right of States or group of States to individual or collective self-defense. Security Council has central role in protection of international peace and security. It decides what kind of measures to be employed: measures not involving the use of armed force or measures involving use of force. The Charter of UN is starting point for any discussion founded in international law, connected with the use of armed force for preservation and restoration of international peace and security. With the aim to elaborate this topic, author researched, assessed, analyzed and compared relevant documents and teachings and afterwards outlined them at highly readable way. International law allows legitimate defense against illegitimate attacks committed not only by the States, but also by non- States actors har-bored by States.